Foreword - Mariusz Gwiazda; Dagmara Wielgosz-Rondolino; Alessandro Poggio (Polish Archaeology in the Mediterranean, 2023)
This volume is the result of a panel held in Warsaw on 8 and 9 June 2022, during the annual conference “Poles in the Near East” organized by the Polish Centre of Mediterranean Archaeology and the Faculty of Archaeology at the University of Warsaw. The panel, entitled “Marble Use, Trade, and Distribution in the Eastern Mediterranean during Late Antiquity”, consisted of 16 papers. Ten of them are included in the proceedings published herein as a special issue of the journal Polish Archaeology in the Mediterranean.